PROSPER MERIMENING “MATEO FALCONE” ASARI TARJIMA VA TAHLILI - Geldiboyeva , S.R.; Axmedov , X.A. (Educational Research in Universal Sciences, 2023)
In this article, we have currently considered the most controversial issue of defense in terms of phraseology that are used in the field of translation studies as well as the combination of words along the path devoted to the translation problem.